Seismic-Based Reservoir Characterization of The Lower Arang Formation in West Natuna Basin Using Acoustic Impedance Inversion and Seismic Attributes - Hakim Afif Putra; Edi Sanjaya; Suwondo; Muhammad Nafian; Praditiyo Riyadi; Widi Atmoko (Testing Center for Oil and Gas LEMIGAS, 2026)
Reservoir characterization is a critical stage in hydrocarbon potential evaluation, particularly for heterogeneous sandstone reservoirs. This study aims to characterize the reservoir of the Lower Arang Formation in the West Natuna Basin using acoustic impedance inversion and seismic attributes. The dataset consists of seismic data and well log data that have been integrated through a well–seismic tie to ensure consistency between time and depth domains. Acoustic impedance inversion was applied to obtain the subsurface impedance distribution, which was then analyzed together with seismic attributes to identify lithological variations and reservoir property indications. The results indicate that zones with relatively low acoustic impedance values correlate well with porous sandstone intervals within the Lower Arang Formation. The integration of inversion results and seismic attributes enhances the delineation of lateral reservoir distribution and supports a more reliable reservoir characterization. This approach provides an effective workflow for reservoir evaluation in clastic systems with similar geological characteristics.